Can shallow groundwater sustain small-scale irrigated agriculture in Sub-Saharan Africa? evidence from N-W Ethiopia - Gowing, J.; Walker, D.; Parkin, G.; Forsythe, N.; Haile, Alemseged Tamiru; Ayenew, D.A. (Elsevier, 2020)
We present an evidence-based approach to identify how best to support development of groundwater for smallscale irrigation in sub-Saharan Africa (SSA). We argue that it is important to focus this effort on shallow groundwater resources. We demonstrate and test this proposal at a case study site: Dangila woreda in the northwestern highlands of Ethiopia. This site was selected to allow exploration of a shallow weathered volcanic regolith type aquifer formation which is found to the South of Lake Tana and also exists more extensively across Ethiopia. We believe lessons from this case study are transferable and there is a case for arguing that shallow groundwater represents a neglected opportunity for promoting sustainable small-scale irrigated agriculture in SSA.